Cytogenetic factors decreasing the fertility of pollen and cobs during clogging of tetraploid maize with triploid grains (Zea mays L.) - E. B. Khatefov; A. A. Grushin; V. N. Boyko (Труды по прикладной ботанике, генетике и селекции)
Background. Clogging of tetraploid maize crops with triploid grains leads to a decrease in grain yield and the destruction of the genome’s stability. Searching for the reasons of the tetraploid genome’s decomposition as well as solving the problem of seed yield reduction in freely pollinated crops of tetraploid maize remains relevant.Materials and methods. Cultivars of tetraploid dentate (k-23427) and sweet (k-23426) maize from VIR and dentate (k-24735) and sweet maize (k-23425) hybrids served as the material of the research. The experiments were carried out in the foothill zone of Kabardino-Balkaria. Incubation and hybridization were carried out under parchment insulators. Metaphase plates of maize roots were stained with Schiff’s reagent according to Feulgen and pollen grains were stained with Lugol’s solution.Results. Triploid grains, along with diploid ones, were able to germinate and show poor fertility. As a result of the fusion between male gametes of triploid and female tetraploid plants, an imbalance in the stability of the tetraploid genome occurred, leading to increased degradation of the cultivar’s productivity with each seed reproduction. A cytological analysis and the results of test crosses ♀2n × ♂3n, ♀4n × ♂3n showed that in self-pollinated triploid plants the frequency of diploid kernel formation was 7.44%; triploid + aneuploidy, 41.78%; tetraploid, 50.74%; and in test crosses the frequency of diploid ones was 18.22%; triploid + aneuploid, 63.83%; and tetraploid, 36.15%. The analysis of segregation classes with the determination of Pearson’s χ2  criterion showed that instead of the expected segregation 1(2n) : 7(3n) + (Xn±1x) : 1(4n), diploid, triploid + aneuploid and tetraploid kernels developed on self-pollinated triploid plants in the ratio of 2 : 13 : 16, respectively, and in test crosses for the 2n and 4n genotypes splitting into diploid, triploid + aneuploid, and tetraploid grains occurred in the ratio of 7 : 18 : 14, respectively.